First-principles investigation of hydrogen behavior in different oxides in ODS steels. (21st June 2019) - Sun, Dan; Ding, Jianhua; Yang, Yaochun; Zhang, Pengbo; Zhao, Jijun
Abstract: The energetics of single and multiple H atoms inside Y2 O3, Y2 Ti2 O7, Y2 TiO5, Y3 Al5 O12 and YAlO3 as well as the migration behavior of H atom have been investigated using first-principles calculations. Among these oxide matrixes, single H atom inside Y2 TiO5 is most energetically stable, followed by Y2 O3, Y2 Ti2 O7, Y3 Al5 O12 and YAlO3 . The migration barrier of H atom in Y2 O3 is lower than that in other oxide crystals. The formation energy and migration barrier of H atom in those oxide crystals are always higher than that in α-Fe. He atom is more stable than H atom inside oxide crystals, contrarily to the trend in α-Fe solid. Generally, in the cases of Hn (1 ≤ n ≤ 4) atoms inside oxide crystals, the formation energy of even-sized Hn cluster is lower than that of odd-sized Hn clusters, because two H atoms form a hydrogen molecule with strong H–H covalent bond. Highlights: H atom inside Y2 TiO5 is most stable, followed by Y2 O3, Y2 Ti2 O7, Y3 Al5 O12, and YAlO3 . H impurity is more difficult to diffuse in oxides than that in Fe matrix. Two H atoms form hydrogen molecule inside oxide crystals.